Flying on the wings of Vollenhoven’s radical Christian worldview: A reconsideration of the usual typology of Christian worldviews - Walt, Barend Johannes van der (Koers, 2012)
This article investigated the traditional typology of Christian worldviews from the perspective of the Christian philosopher, D.H.Th. Vollenhoven (1892?1978). The usual categorisation started by Niebuhr (in 1951), and adopted by some Reformational scholars afterwards, is questioned as too simplistic, forcing Christian thinkers and schools of thought into five pigeonholes. Worldviews ? including the Christian ones ? are complex phenomena. They should not be considered, for example, as merely logical systems or aesthetic ’stories’. Vollenhoven’s systematic philosophy and historiography of philosophy (his thetical-critical approach) can provide some clues for a new way to describe different Christian worldviews, as well as to arrive at the outlines of a more radical and comprehensive Christian worldview based on God's threefold creational, inscripturated and incarnated revelation.